Determinación de los Microorganismos Eficientes para la Remoción del Valor de la DBO en las Aguas Residuales Domésticas de la localidad de Jepelacio - Vasquez Tarrilllo, Alex (2017)
In front of the need for an effective treatment for wastewater that is generated daily and are downloaded to any surface source without giving proper treatment, we find microorganisms efficient (I) such as debuggers of wastewater, the present research tries to demonstrate the effect of the efficient microorganisms in the removal of the value of the BOD of residual waters. Samples of the domestic residual water of the facultative lagoons (control) start date and of the experimental units (treatments) after the 10 days to inoculate microorganisms efficient, analyzing the concentration of the biochemical oxygen demand. Under the conditions of the present study, the results showed differences in each sample of each block, both in the control and in the treatments: the efficiency of removal of the BOD value with the dose of 5 mL of ME had an average of 84, 44%, decreasing on average the concentration of BOD from 460.5 to 71.83, with the 10 mL dose of ME had a mean removal of 93.33%, decreasing on average the concentration from 460.5 to 30.83 and With the 15 mL dose of ME had a mean removal of 89.73%, decreasing on average the concentration of BOD from 460.5 to 47.41. The present investigation concludes that, by applying efficient microorganisms, a high removal of the BOD value was achieved with the dose of 10 ml of efficient microorganisms, being the most optimum, with an average level of acceptability of 93.33% according to the Maximum Limits Permissible for domestic wastewater.